Divided we stand : American workers and the struggle for Black equality - Nelson, Bruce, 1940-2022 (Politics and society in twentieth-century America., 2001)
"Divided We Stand is a study of how class and race have intersected in American society - above all, in the "making" and remaking of the American working class in the nineteenth and twentieth centuries. Focusing mainly on longshoremen in the ports of New York, New Orleans, and Los Angeles, and on steelworkers in many of the nation's steel towns, it examines how European immigrants became American and "white" in the crucible of the industrial workplace and the ethnic working-class neighborhood."